Management of premature rupture of the membrane - Risanto Siswosudarmo Risanto Siswosudarmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
A literature study on the management of premature rupture of the membrane (PROM) is carried out to find out the best method and its impact on maternal and neonatal morbidity.PROM is defined as rupture of the fetal membrane before the onset of true labor. The incidence of PROM varies from 0,7 to 10%. Premature labor and its consequences to the newborn as well as maternal and neonatal infections are complications attributed to early rupture of the membrane.Conservative management for PROM before 37 weeks of gestation is a method used by most obstetricians. Patients should be staying in bed as long as the amniotic fluid is still coming out, no vaginal examination performed, and she should be closedly monitored for signs of infection and prophylac tic antibiotics given. Once the signs of i nfection develop, termination of pregnancy should be carried out and massive antibiotics should be given. Risk of infection becomes evident if rupture of the membrane goes beyond 12 to 24 hours so that prophylactic antibiotics should be given before 12 hours of rupture. Most of the cases will go to labor before 48 hours, although in some cases labor can be postponed for 19, 33, 39, 44, and 55 days. If labor can be postponed for more than 48 hours, the risk of suffering From respiratory distress syndrome (RDS) in neonates is getting lower.The management of premature rupture of the membrane after 37 weeks of gestation depends on the condition of the cervix. Patients with ripe cervix can be induced immediately, but patients with unripe cervix should be managed conservatively.Key Words: PROM - RDS - prophylactic antibiotics - perinatal mortality - maternal infection